The Role of Mutation Rates of GNAQ or GNA11 in Cases of Uveal Melanoma in Japan. Issue 9 (October 2018) - Ominato, Jun; Fukuchi, Takeo; Sato, Ayako; Yamaguchi, Naoyuki; Kobayashi, Kazue; Cho, Hiroyuki; Oyama, Tokuhide; Ajioka, Yoichi
Abstract : GNAQ and GNA11 mutations are thought to be important for the tumorigenesis of uveal melanoma. Although previous studies have reported on mutation rates in cases of uveal melanoma, presently, no such report for the Japanese population exists. In this study, we examined the frequency of GNAQ and GNA11 somatic mutations in cases of uveal melanoma in Japan and their relationship with clinicopathologic features or Ki-67-positive cell rates (Ki-67 labeling index: Ki-67 LI) using immunofluorescence methods. The study involved 19 cases of uveal melanoma. We extracted the template DNA from formalin-fixed, paraffin-embedded specimens using a DNA extraction kit. We amplified the DNA sequences of GNAQ and GNA11 using polymerase chain reaction and analyzed mutations by direct sequencing. We evaluated Ki-67 LI using immunofluorescence methods. The frequencies of GNAQ and GNA11 somatic mutations were 26.3% (5/19) and 31.6% (6/19), respectively. The GNAQ and GNA11 mutations were mutually exclusive, as indicated in previous reports. The frequency of GNA11 mutations was significantly higher in epithelioid cells; however, no significant association between GNAQ mutations and cell type was evident, and there was no significant difference in Ki-67 LI between the mutation-positive and mutation-negative tumors. GNAQ and GNA11 mutations were identified in cases of uveal melanoma in Japan, although at lower frequencies than in white counterparts. The mutation frequency of GNA11 was significantly higher in epithelioid cells.